Calcium in Brugada Syndrome: Questions for Future Research - Monasky, Michelle M.; Pappone, Carlo; Piccoli, Marco; Ghiroldi, Andrea; Micaglio, Emanuele; Anastasia, Luigi (Frontiers in Physiology, 2018)
The Brugada syndrome (BrS) is characterized by coved-type ST-segment elevation in the right precordial leads on the electrocardiogram (ECG) and increased risk of sudden cardiac death. While it is an inheritable disease, determining the true prevalence is a challenge, since patients may report no known family history of the syndrome, present with a normal spontaneous ECG pattern at the time of examination, and test negative for all known BrS-causative genes. In fact, sudden cardiac death is often the first indication that a person is affected by the syndrome. Men are more likely to be symptomatic than women. Abnormal, low-voltage, fractionated electrograms have been found in the epicardium of the right ventricular outflow tract. Ablation of this area abolishes the abnormal electrograms and helps to prevent arrhythmic recurrences. BrS patients are more likely to experience ventricular tachycardia/fibrillation during fever or during an increase in vagal tone. Isoproterenol helps to reverse the ECG BrS phenotype. In this review, we discuss roles of calcium in various conditions that are relevant to BrS, such as changes in temperature, heart rate, and vagal tone, and the effects of gender and isoproterenol on calcium handling. Studies are warranted to further investigate these mechanisms in models of BrS.